1998
DOI: 10.1136/adc.79.3.263
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcome of brain manganese deposition in patients on home parenteral nutrition

Abstract: Manganese intoxication has been described in children on long term parenteral nutrition presenting with liver and nervous system disorders. Cases are reported of a brother and sister on long term parenteral nutrition with hypermanganesaemia and basal ganglia manganese deposition, detected by magnetic resonance imaging (MRI), without overt neurological signs. Following reduction of manganese intake, basal ganglia manganese was monitored by repeated MRI, and neurological and developmental examinations. An MRI in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 12 publications
1
44
0
Order By: Relevance
“…In two patients receiving long-term parenteral nutrition, a reduction in Mn intake was followed by regression of MRI changes with concomitant decreases in whole blood Mn from 1.8 lg/dl and 2.8 lg/dl to 1.4 lg/dl and 1.2 lg/dl respectively [7]. We recommend that children with congenital PSVS who face the prospect of Mn exposure throughout life, should avoid excessive intake of foods rich in Mn, e.g.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In two patients receiving long-term parenteral nutrition, a reduction in Mn intake was followed by regression of MRI changes with concomitant decreases in whole blood Mn from 1.8 lg/dl and 2.8 lg/dl to 1.4 lg/dl and 1.2 lg/dl respectively [7]. We recommend that children with congenital PSVS who face the prospect of Mn exposure throughout life, should avoid excessive intake of foods rich in Mn, e.g.…”
Section: Discussionmentioning
confidence: 94%
“…MRI abnormalities in the basal ganglia have been shown to be reversible [1,7,10]. In two patients receiving long-term parenteral nutrition, a reduction in Mn intake was followed by regression of MRI changes with concomitant decreases in whole blood Mn from 1.8 lg/dl and 2.8 lg/dl to 1.4 lg/dl and 1.2 lg/dl respectively [7].…”
Section: Discussionmentioning
confidence: 97%
“…Withdrawal from the TPN solutions significantly decreases Mn levels in both the blood and CNS (Bertinet et al, 2000). In children chronically receiving TPN high Mn blood levels and abnormal neurological signs have been reported, along with MRI findings indicative of Mn deposition in the brain (Kafritsa et al, 1998). Once removed from Mn supplemented TPN, Mn brain levels tend to decline over time, blood Mn levels normalize and some case reports suggest a good prognosis without long-lasting neurodevelopmental sequelae (Kafritsa et al, 1998).…”
Section: Parenteral Exposurementioning
confidence: 99%
“…John Couper was the first to report neurological effects associated with exposure to Mn in 1837, when he described muscle weakness, limb tremor, whispering speech, salivation, and a bent posture in five men working in a Mn ore crushing plant in France [6]. With the advent of MRI and PET scans it has become possible to correlate the clinical and laboratory findings with structural abnormalities.…”
Section: Discussionmentioning
confidence: 98%
“…Imaging and autopsy studies indicate that Mn accumulates in the globus pallidus, putamen, thalamus, subthalamic nuclei, pituitary, and occasionally in cortical areas. Of interest, patients may have MRI evidence of Mn accumulation without clinical findings [3,6]. In a small prospective MRI study of patients receiving TPN all patients were found to have MRI evidence of Mn deposition but only one out of 11 had clinical symptoms [3].…”
Section: Discussionmentioning
confidence: 99%